Effect Of Service Features, Price, And Service Quality on Online Customer Satisfaction: Study on InDrive application service users in Bandung - Mubarok, Dadan Abdul Aziz; Hajar, Asri Shopiatul; Karamang, Ezra; Sarah, Siti; Akbar, Ridho Riadi (Universitas Indonesia Membangun (Inaba), 2024)
The purpose of this research is to determine the influence of service features, price and service quality on customer satisfaction of InDrive application service users in Bandung. The method used in this research is a quantitative method with a descriptive and verification approach. The type of data is primary and secondary research data obtained from distributing questionnaires to customers using the InDrive application service. The samples used were 100 respondents. The sampling technique in this research used the Probability Sampling technique. The data analysis methods used are Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Test, Correlation Coefficient Analysis, Determination Coefficient Analysis and Hypothesis Testing. Descriptive research results show that respondents' responses to Service Features (X1), Price (X2) and Service Quality (X3) resulted in relatively poor ratings. Based on partial test results, the Service Feature variable has a t-value of 2.065 > 1.98498 and a sig value of 0.042 < 0.05. Then the Price variable has a t-count of 3.004 > 1.98498 and a sig value of 0.003 < 0.05. And the Service Quality variable has a t-value of 0.429 < 1.98498 and 0.669 > 0.05.